Innovations in Islamic Religious Education Assessment In The Society 5.0 Era at MAN 3 Padang Panjang - Yemmardotillah, M.; Rahmi, Elvi; Asrizallis, Asrizallis; Indriani, Rini (Jurnal Kawakib, 2024)
This study examines the innovation of Islamic Religious Education (PAI) assessment in the Society 5.0 era, focusing on the integration of technology and Islamic values. The research aims to identify forms of PAI assessment innovation, analyze implementation challenges, and formulate optimization strategies. Using a qualitative approach with a case study design, the research was conducted in selected schools/madrasahs, involving PAI teachers, students, and Islamic education experts as research subjects. Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed using thematic analysis techniques. The results show that PAI assessment innovation has evolved from the use of simple digital platforms to the implementation of Artificial Intelligence (AI) and virtual reality technology. The integration of Islamic values in technology-based assessments is realized through the application of digital integrity principles, development of assessments promoting noble character, and incorporation of the tazkiyatun nafs concept in digital self-assessment. The main challenges in implementation include infrastructure limitations, teacher and student readiness, and concerns about over-reliance on technology. Strategies developed to overcome these challenges include digital competency enhancement programs for PAI teachers, collaboration with technology experts, and a phased approach to innovation implementation. Stakeholder perceptions of PAI assessment innovation tend to vary, with students showing enthusiasm, while teachers and parents have more cautious views.